PERAN GENDER MASYARAKAT PAPUA DALAM USAHATANI PANGAN - yolanda holle (Jurnal Harkat : Media Komunikasi Gender, 2020)
Abstract. The focus of this research is the role of gender in Papuan society in food farming. This is intended to increase the participation of women and men human resources in various physical activities and decision making to jointly create gender equality and justice. The research aims to (1) analyze gender roles in role activities, access, control, benefits and (2) analyze the factors that cause gender roles. The study was conducted in the District of Teluk Wondama, with 106 respondents. The method used in this study is a survey method with in-depth interview technique, and analyzed using the Harvard method. The results of the study concluded that, (1) gender bias towards men in the role profile at the seed procurement and fence-making stages. (2) gender bias towards women in the role profile at the stages of selling the results, (3) gender bias towards women in making decisions to be involved in  the whole stage of farming, (4) gender bias towards women in the control profile at decision making for control of land resources, (5) there is no gender bias in the profile of access to farm resources, and (6) there is no gender bias in the profile of benefits to farm resources. Factors causing gender roles include (1) understanding of social values of society about feminism and masculine, (2) patriarchal kinship system, and (3) dowry values in Papuan society.Abstrak. Fokus penelitian ini adalah peran gender pada masyarakat Papua dalam usahatani pangan.  Hal ini dimaksudkan guna meningkatkan partisipasi sumberdaya manusia perempuan dan laki-laki dalam berbagai aktifitas fisik maupun pengambilan keputusan untuk bersama-sama menciptakan kesetaraan dan keadilan gender.  Penelitian bertujuan untuk (1) menganalisis peran gender dalam aktifitas peran, akses, kontrol, manfaat dan (2) menganalisis faktor-faktor penyebab peran gender.  Penelitian dilakukan di Kabupaten Teluk Wondama, dengan jumlah responden sebanyak 106 orang. Metode yang dipakai dalam penelitian ini adalah metode survey dengan teknik wawacara mendalam, dan dianalisis dengan menggunakan metode harvard. Hasil penelitian menyimpulkan bahwa, (1) bias gender terhadap laki-laki pada profil peran dalam tahap pengadaan bibit dan pembuatan pagar. (2) bias gender terhadap perempuan pada profil peran dalam tahapan penjualan hasil, (3) bias gender terhadap perempuan dalam mengambil keputusan untuk terlibat dalam keseluruhan tahap usahatani, (4) bias gender terhadap perempuan pada profil kontrol dalam pengambilan keputusan akan penguasaan sumberdaya tanah, (5) tidak terjadi bias gender pada profil akses terhadap sumberdaya usahatani, dan (6) tidak terjadi bias gender pada profil manfaat terhadap sumberdaya usahatani.  Faktor penyebab peran gender antara lain (1) pemahaman nilai sosial masyarakat tentang feminisme dan maskulin, (2) sistim kekerabatan patriakal, dan (3) nilai  mas kawin pada masyarakat Papua.